STUDI KRITIS JUAL BELI DEKORASI UANG MASKAWIN - Muhammad Arifin Badri (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2018)
This study aims to examine the laws of dowry money decoration that are common in the community. The innovation and soul of art that is channeled through décor of dowry money is proven to produce beautiful and unique works, so as to attract the attention and interest of the wider community. However, because to produce beautiful and unique works, a high level of creativity is needed, so not everyone can do it. On the one hand, this phenomenon opens up quite good business opportunities, but on the other hand, it should be watched out, because in some conditions it contains the practice of buying and selling currencies with nominal differences. Through this study, I would like to uncover the law of buying and selling practices decorating dowry money and decorating services. As I also intend to present an applicative solution for the community so that they can still channel their artistic talents without violating Shari’ah law.